2010
DOI: 10.1007/s13237-010-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative karyomorphological analyses of in vitro and in vivo grown plants of Aloe vera L. BURM. f.

Abstract: Aloe vera L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
(24 reference statements)
2
15
1
1
Order By: Relevance
“…According to Stebbins (1971) karyotype asymmetry of A. vera is 3B type. These fi ndings support earlier observations of chromosome constitution for A. vera (Sapre 1978;Das et al 2010; Gunjan and Roy 2010).…”
Section: Karyomorphology Of Mitotic Metaphase Chromosomessupporting
confidence: 92%
See 1 more Smart Citation
“…According to Stebbins (1971) karyotype asymmetry of A. vera is 3B type. These fi ndings support earlier observations of chromosome constitution for A. vera (Sapre 1978;Das et al 2010; Gunjan and Roy 2010).…”
Section: Karyomorphology Of Mitotic Metaphase Chromosomessupporting
confidence: 92%
“…Yet, its importance is partly associated with general interest in plant reproduction and fertility and partly with greater understanding of genome constitution and its exploitation. In contrast to spontaneous mitotic chromosomal aberrations (Vig 1968;Sapre 1975), somatic chromosome characteristics (Sapre 1978;Umesh and Ranganath 2003;Das et al 2010), including the fl uorescent metaphase chromosomes (Alam and Khanam 2005) reported earlier throwing light on the structure and behaviour of mitotic chromosomes, meiotic behaviour especially of prophase I chromosomes is inadequate. The present study aims at providing a comprehensive account of the structure and behaviour of meiotic as well as mitotic chromosomes of A. vera.…”
mentioning
confidence: 99%
“…Finally, a photoplate karyogram of each species was prepared with the help of Adobe Photoshop version 7.0 (Ghosh and Datta 2006). Karyotype details of the two selected Aloe species have been worked out (Das et al 2010) and presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Actualmente se reportan 400 especies de Aloe (IASC, 2008), de las cuales A. barbadensis y A. arborescens var. natalensis Berger, son las únicas especies cultivadas comercialmente (Das et al, 2010).…”
Section: Introductionunclassified
“…Early last century, products like leaf powder, gel and juice had a high demand from the medical and cosmetic industry of the United States and Europe, which encouraged the establishment of plantations in Mexico, Texas, Dominican Republic, Haiti and Namibia (Añez and Vásquez, 2005). Currently 400 species of Aloe are reported (IASC, 2008), of which A. barbadensis and A. arborescens var natalensis Berger, are the only species commercially cultivated (Das et al, 2010).…”
Section: Introductionmentioning
confidence: 99%